Egg characteristics vary longitudinally in Arctic shorebirds - Jin Liu; Ziwen Chai; Hui Wang; Anton Ivanov; Vojtěch Kubelka; Robert Freckleton; Zhengwang Zhang; Tamás Székely (iScience, 2023)
Summary: Arctic environments are changing rapidly and if we are to understand the resilience of species to future changes, we need to investigate alterations in their life histories. Egg size and egg shape are key life-history traits, reflecting parental investment as well as influencing future reproductive success. Here we focus on egg characteristics in two Arctic shorebirds, the Dunlin (Calidris alpina) and the Temminck’s stint (Calidris temminckii). Using egg photos that encompass their full breeding ranges, we show that egg characteristics exhibit significant longitudinal variations, and the variation in the monogamous species (Dunlin) is significantly greater than the polygamous species (Temminck’s stint). Our finding is consistent with the recent “disperse-to-mate” hypothesis which asserts that polygamous species disperse further to find mates than monogamous species, and by doing so they create panmictic populations. Taken together, Arctic shorebirds offer excellent opportunities to understand evolutionary patterns in life history traits.